Seasonal variation in bioactive properties and phenolic composition of cardoon (Cynara cardunculus var. altilis) bracts - Mandim, Filipa (2018)
Cardoon (Cynara cardunculus L.) bracts were collected at different maturation stages to investigate seasonal changes in the phenolic compounds profile and in vitro bioactivities. Among the 12 phenolic compounds tentatively identified, 3,5-O-dicaffeoylquinic acid (21.83 mg/g extract) and apigenin-7-O-glucuronide (10.6 mg/g extract) were the most abundant. Immature bracts (C1: principal growth stage (PGS) 5) had the highest phenolic compounds content, and anti-inflammatory (IC50 = 72 µg/mL) and cytotoxic (GI50 of 30–79 µg/mL) activities. Moreover, extract C1 inhibited efficiently the formation of thiobarbituric acid reactive substances (TBARS; IC50 = 26.8 µg/mL), while extract C8 (PGS 8/9) was more effective against oxidative haemolysis (IC50 38 and 75 µg/mL). The highest antibacterial and antifungal activities were attributed to samples C1 and C6 (PGS 7/8) and samples C2 (PGS 5/6) and C4 (PGS 6/7), respectively. Overall, the obtained results suggest the seasonal changes of polyphenolic composition and bioactivity of cardoon bracts of variable maturity.